2015
DOI: 10.1063/1.4926455
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the structure of topological insulator thin films

Abstract: We describe the characterization of structural defects that occur during molecular beam epitaxy of topological insulator thin films on commonly used substrates. Twinned domains are ubiquitous but can be reduced by growth on smooth InP (111)A substrates, depending on details of the oxide desorption. Even with a low density of twins, the lattice mismatch between (Bi,Sb) 2 Te 3 and InP can cause tilts in the film with respect to the substrate. We also briefly discuss transport in simultaneously top and back elect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…2e) shows a peak repetition of 60 o , indicating the twin domains are formed in our Sn 0.9 Cr 0.1 Te (111) film. Previous studies have demonstrated the (Bi,Sb) 2 Te 3 film grown on SrTiO 3 (111) substrate has the twin domain structures [38,39], so the two domains found in our Sn 0.9 Cr 0.1 Te (111) film is very likely due to the buffer film of 1QL (Bi 0.2 Sb 0.8 ) 2 Te 3 . The QAH state has been successfully realized in the Cr-and Vdoped (Bi,Sb) 2 Te 3 film grown on the SrTiO 3 (111) substrates [3,15], so it is very likely that the twin domains structures in our Cr-doped SnTe (111) will not affect the realization of the high-Chern-number QAH state.…”
mentioning
confidence: 77%
“…2e) shows a peak repetition of 60 o , indicating the twin domains are formed in our Sn 0.9 Cr 0.1 Te (111) film. Previous studies have demonstrated the (Bi,Sb) 2 Te 3 film grown on SrTiO 3 (111) substrate has the twin domain structures [38,39], so the two domains found in our Sn 0.9 Cr 0.1 Te (111) film is very likely due to the buffer film of 1QL (Bi 0.2 Sb 0.8 ) 2 Te 3 . The QAH state has been successfully realized in the Cr-and Vdoped (Bi,Sb) 2 Te 3 film grown on the SrTiO 3 (111) substrates [3,15], so it is very likely that the twin domains structures in our Cr-doped SnTe (111) will not affect the realization of the high-Chern-number QAH state.…”
mentioning
confidence: 77%
“…A control sample was grown on (111)-oriented InP to rule out optical gating effects intrinsic to the (Bi,Sb) 2 Te 3 material. The MBE growth and characterization of TI materials on SrTiO 3 and InP are discussed in detail in a separate article ( 41 ). Identically prepared bare SrTiO 3 substrates were measured to control for substrate photoconductivity.…”
Section: Methodsmentioning
confidence: 99%
“…Amorphous Te or Se has been already widely used as capping layers for TI materials. [ 43–46 ] However, it often remains unclear whether the intrinsic topological properties are influenced by the overlayer, but some studies report on alterations of the stoichiometry after the removal of a Te or Se capping layer. [ 43,44 ]…”
Section: Electronic Structure and Transport Properties: In Situ Versumentioning
confidence: 99%